Management of Zakat Ar-Riqab in Rumah Pemulihan Akhlak Insani (INSANI) / Nur Syaza Syazwani Mohd Shahril. - Mohd Shahril, Nur Syaza Syazwani (2019)
Zakat are the obligation of giving a portion of an individual's wealth and possessions for primarily charitable purposes. In this research, it is specify in zakat distribution to Ar-Riqab’s community. Therefore, the study was conducted at Pusat Pemulihan Akhlak INSANI, Selangor. This study reviews the form of zakat that given by Majlis Agama Islam Selangor (MAIS) and to identify zakat funds are used in program. Data and information obtained through documentation and interviewing methods with INSANI’s counsellor, then analysed using the comparative and deductive method. The finding shows that the overall of the distribution of zakat Ar-Riqab are distributed mostly in two forms which is in assist in monetary and assets given.